A systematic review of disability, rehabilitation and lifestyle services in rural and remote Australia through the lens of the people-centred health care. Issue 20 (25th September 2022) - Bohanna, India; Harriss, Linton; McDonald, Malcolm; Cullen, Jennifer; Strivens, Edward; Bird, Katrina; Blanco, Leisyle; Thompson, Fintan; Wapau, Hylda; Wason, Alan; Barker, Ruth
Abstract: Purpose: The aim of this systematic review was to identify models of community disability, rehabilitation and lifestyle service delivery in non-metropolitan areas of Australia, and to describe these models through an Integrated People-Centred Health Services (IPCHS) lens. Materials and methods: We identified peer-reviewed studies published between 2000 and June 2021 that met the following criteria: described or evaluated a community service delivery model, intervention or program in regional, rural or remote Australia; provided for people with a disability or a potentially disabling health condition. A scoring rubric was developed covering the five IPCHS strategies. Results: Nineteen studies were included in the review. We identified a range of service delivery models providing support to people with a range of disabilities or conditions. We report evidence of the use of the IPCHS strategies in ways relevant to the local context. Discussion: Several strengths emerged, with many services tailored to individual need, and significant community engagement. Innovative rural service delivery approaches were also identified. Key areas requiring action included improved coordination or integration within and across professions and sectors. There was limited evidence of co-production of solutions or participatory governance. While people-centred approaches show promise to improve community-based services, large-scale fundamental change is required. IMPLICATIONS FOR REHABILITATION: Community-based disability and rehabilitation services in rural and remote Australia performed well at delivering tailored care and engaging in community consultation. These services must urgently implement strategies to enhance community ownership of solutions and participatory governance. Services must place a greater focus on explicit strategies to integrate and coordinate across services and professions, and to create an enabling environment, to deliver people-centred care. The World Health Organisation Integrated People-Centred Health Services framework provides an important roadmap to improving service delivery in rural and remote Australian communities.